2021
DOI: 10.1186/s42506-021-00095-w
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of vitamin C in the management of COVID-19: A Review

Abstract: Background The outbreak of coronavirus infectious disease-2019 (COVID-19) is globally deemed a significant threat to human life. Researchers are searching for prevention strategies, mitigation interventions, and potential therapeutics that may reduce the infection’s severity. One such means that is highly being talked in online and in social media is vitamin C. Main text Vitamin C is a robust antioxidant that boosts the immune system of the human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Therefore, it is required to collect all studies performed worldwide and carefully synchronize them to establish standard treatment options using vitamin C. 68 Moreover, to develop strong immunity against coronavirus infection, it is recommended that patients should administer vitamin C on a regular basis. A study by Uddin et al 32 recently suggested that the requirement of vitamin C is enhanced in infected individuals and daily intake of vitamin C (1–2 g/day) is recommended in such conditions. It is also needed to be mentioned that 200 mg/day dose of vitamin C is a prerequisite to maintaining saturated blood levels in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is required to collect all studies performed worldwide and carefully synchronize them to establish standard treatment options using vitamin C. 68 Moreover, to develop strong immunity against coronavirus infection, it is recommended that patients should administer vitamin C on a regular basis. A study by Uddin et al 32 recently suggested that the requirement of vitamin C is enhanced in infected individuals and daily intake of vitamin C (1–2 g/day) is recommended in such conditions. It is also needed to be mentioned that 200 mg/day dose of vitamin C is a prerequisite to maintaining saturated blood levels in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation and severe respiratory infections have been found in vitamin C‐deficient persons during COVID‐19. 31 , 32 The efficacy of an elevated dose of vitamin C in individuals with SARS‐CoV‐2 has been studied in various contexts and clinical findings. The effects of high dose intravenous vitamin C (HDIVC) with a placebo in a randomized controlled trial pilot study to see if HDIVC infusion was effective against severe COVID‐19 and found that HDIVC failed to reduce mortality in the hospital or improve the number of days without invasive mechanical breathing after 28 days of use.…”
Section: Introductionmentioning
confidence: 99%
“…It also stimulates caspase-dependent apoptosis, boosting macrophage uptake and clearance, and suppresses necrosis, including NETosis, promoting inflammatory resolution and reducing tissue damage). (B) Amount of vitamin C in selected fruits (per 100 g) ( 124 126 ).…”
Section: Vitamins and Food Supplements To Enhance Immunity Against Vi...mentioning
confidence: 99%
“…2 By attaching to the angiotensin‐converting enzyme 2 receptor, this virus is hypothesized to enter the respiratory system via contaminated droplets or mucosal contact. 3 Even though most COVID‐19 sufferers are asymptomatic, some individuals die from severe pneumonia, acute respiratory distress syndrome (ARDS), and multiorgan failure due to COVID‐19 infection. 4 , 5 According to existing research, SARS‐CoV‐2 predominantly infects the upper respiratory system before progressing to the lower airways.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, about 1,951,504 cases have been identified, and 29,122 patients have died due to COVID‐19 infection till March 30, 2022 2 . By attaching to the angiotensin‐converting enzyme 2 receptor, this virus is hypothesized to enter the respiratory system via contaminated droplets or mucosal contact 3 . Even though most COVID‐19 sufferers are asymptomatic, some individuals die from severe pneumonia, acute respiratory distress syndrome (ARDS), and multiorgan failure due to COVID‐19 infection 4,5 .…”
Section: Introductionmentioning
confidence: 99%